THE FOOD AND FEEDING HABITS OF THE GREY MULLETS, MUGIL PARSIA HAMILTON AND M. SPEIGLERI BLEEKER - Sarojini, K K (Indian Journal of Fisheries, 2016)
In an earlier paper, the author (Sarojini, 1951) reviewed the existing knowledgeon the food and feeding habits of grey mullets and the diverse views heldby previous workers. Three more contributions have since then beenpublished in India, containing further information on this subject. Bapatand Bal*(1952) have stated that copepods constitute the main food ofM. parsia in Bombay waters, which is supplemented by diatoms and organicmatter taken along with mud